FAKTOR PENENTU KEPUTUSAN WISATAWAN DOMESTIK DALAM MEMILIH AKOMODASI DI DESA WISATA CANGGU SEBAGAI TEMPAT STAYCATION - Diah Kesumadewi, Putu; Manik Pertiwi, AA. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023)DO - 10.24843/IPTA.2023.v11.i02.p01, 2023)
The Covid 19 pandemic has caused the tourism sector to experience a decline due to reduced tourist activity. One of the government regulations to avoid crowds makes most people prefer to stay at home longer. To continue to comply with government regulations to avoid crowds, some people can still carry out tourist activities by staying in accommodation that is close to where they live. This habit is known as a staycation. Canggu Tourism Village is one of the destinations that is popular with domestic tourists for staycation activities. This research aims to examine and analyze the determining factors in domestic tourists' decisions in choosing accommodation in the Canggu Tourism Village as a staycation location. This research used 100 respondents with purposive sampling. Data will be analyzed using quantitative descriptive analysis and using factor analysis. Based on the results of calculations using factor analysis, there are 16 variables which are grouped into 4 factors, namely push and pull factors, recommendation factors and social media, self-motivation and the location and atmosphere of accommodation in the Canggu Tourism Village. Providing accommodation services with a staycation concept must be well organized and always innovated so that tourists will return to visit this village.